Cybercrime Punishment Formulation Using Methods DDoS Attack Regarding Websites from a Positive Legal Perspective - Eko Wahyu Ramadani; Rustam Dahar Karnadi Apollo Harahap; Riza Fibriani (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
Cybercrime using the DDoS attack method against a website is a crime to paralyze a website by flooding the webserver traffic so that the webserver experiences overload and the website system is damaged. This research aims to analyze the criminal sanctions for DDoS attacks on websites from a Positive Legal Perspective. The type of research used is normative research, the approach used uses a statute approach. The act of DDoS attack on a website in Indonesian positive law is included in an unlawful act as regulated in Article 332 paragraph (3) of the Criminal Code (KUHP), Article 30 paragraph (3) and Article 33. Criminal sanctions for cybercrimes using methods DDoS attacks are contained in Article 46 paragraph (3) and Article 49 of Law Number 01 of 2024 concerning the second amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions